Speed-related isokinetic and psychophysical responses of female military personnel - Kennedy, Dale Charles (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2002)
The present study aims to contribute in an area that has long been neglected, the indigenous female population, about whose physical strength and work-capacity very little is known. Speed-related isokinetic and psychophysical responses of female military personnel were assessed (N=32). Furthermore benchmark data was established for Work-Simulation isokinetic responses where there appears to be limited publication. Analysis of the data showed significant differences in torque, work and power outputs as velocity increased. Only wrench-turning left and right rotation for peak torque and total work did not show significant reductions. Consistency of effort level recorded an average of 72% across the selected isokinetic tests. No discernible morphological and strength expression differences were observed between military office workers and infantry personnel, and no significant correlations were recorded between heart rate and RPE values.
Keywords: Uncatalogued